ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PRESTASI MAHASISWA DALAM MEMPELAJARI MATAKULIAH AKUNTANSI KEUANGAN MENENGAH (Studi empiris pada mahasiswa Jurusan Akuntansi Reguler di Fakultas Ekonomika dan Bisnis Universitas Diponegoro tahun angkatan 2009 dan 20 - Donny Iskandarsyah; Imam Ghozali (Diponegoro Journal of Accounting, 2012)
This study is a combination of previous researches conducted by Elaine Waples and Darayseh Moses (2005), Savanid Vatanasakdakul and Andi Choun (2010), and Isni Ischayanti (2011). This study aims to analyze the factors that affect students’ performance in Intermediate Accounting because many students experienced difficulty by understanding in Intermediate Accounting, so it affects the ability of the students and achievement in grade directly. The purpose of this study was to obtain empirical evidences: how the teaching style, assistance to students, course structure, and teaching-and-learning-facilities-provided-by-the-faculty affect the ability of students to learn and understand well in Intermediate Accounting in the scope of the Accounting Department, Faculty of Business and Economics, Diponegoro University. This study population are students of Accounting Department, Regular Program, Faculty of Business and Economics, Diponegoro University, batch 2009 and 2010 who have taken Intermediate Accounting II. The sample are students majoring in Accounting, Regular Program, Faculty of Business and Economics, Diponegoro University, amounting to 191 respondents and eligible respondents totaled 179. Sampling technique is using the Rea Parker formula with information-gathering techniques (data) be a list of statements distributed in the form of questionnaires. From this research, it can be concluded that the hypothesis: first, teaching style has a positive and significant impact on students’ performance in Intermediate Accounting, second, assistance to students has a positive and significant impact on student achievement in Intermediate Accounting, third, course structure has a positive and significant impact on students’ performance in Intermediate Accounting, and teaching-and-learning-facilities-provided-by-the-faculty has a positive and significant impact on students’ performance in Intermediate Accounting. From this results of this study are expected to contribute empirical perception students to understand Intermediate Accounting nowaday and can also be used to motivate students in order to have high integrity and properly understand Intermediate Accounting.